IOC makes biggest esports statement yet with launch of Olympic Virtual Series - Palmer, D. (inside the games, 2021)
According to the IOC, the OVS will "mobilise virtual sport, esports and gaming enthusiasts all around the world in order to reach new Olympic audiences".